2x * x^2 = 2x^3.
Multiply the parts that are alike. The first term has a coefficient of 2, the second term has a coefficient of 1 (x = 1*x). The first term has variable x (which is x^1), the second term has variable x^2. Since they have the same base (both are x), we can add the powers together (x^2 = x * x, so x * x^2 = x * x * x = x^3)
(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.
It is: -2x squared
2x2 + 2x = 2x(x+1)
x^2+2x^2=3x^2
The answer to x2 - 2x - 4y2 - 4y =(x - 2y)(x - 2y - 2)
2x² multiplied by 5 = 10x²
To find the product of x squared and 2x squared, you multiply the coefficients (2 and 1) to get 2, and then add the exponents of x (2 and 2) to get x to the power of 4. Therefore, x squared times 2x squared is equal to 2x^4.
(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.
No. x squared is x times x, whereas 2x is x + x.
If you mean: (2x-7y)(x+y) then it is 2x squared -5xy -7y squared
x2 - 2x = x(x-2)
2x2 ÷ x = 2x
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
Add the x's squared together to get 2x^2+x. You cannot add anymore so the answer is 2x^2+x
It is: -2x squared
2x2 + 2x = 2x(x+1)
2 squared X 3 squared = 5 squared